Gall bladder stones and the associated histopathology– a tertiary care centre study - Pillai, Vijayakumaran; Sreekantan, Renjith; Chisthi, Meer M. (International Journal of Research in Medical Sciences, 2017)
Background: Gall stones form one of the main reasons for recurrent upper abdomen pain. Cholecystectomy has turned out to be one of the commonest laparoscopic procedures done all over the world. The objectives of the study were to analyse the histopathological changes in gallstone disease and to study the clinical and biochemical factors that are seen in gall stone disease. Methods: This was a hospital based cross sectional study conducted at a tertiary care centre from January 2013 to December 2014. 108 patients admitted with diagnosis of cholelithiasis and posted for cholecystectomy were studied. Their clinical and biochemical data and post-operative stone analysis results and histopathological reports were collected and analyzed. Results: 63% of the patients were females with a female to male ratio of 1.7:1. Of the group, 64.8% had a BMI between 25 and 29.9. 65.7% patients got operated within one year of the onset of symptoms. Serum cholesterol levels were found elevated in majority of patients. 61% patients had multiple gall stones. 62% had stones composed of cholesterol, bilirubin, calcium carbonate and calcium oxalate. 102 out of the 108 specimens showed histological features of chronic cholecystitis only. One case showed a premalignant change in the form of pyloric metaplasia. Conclusions: Cholelithiasis is seen mostly in females, most of them having elevated cholesterol levels. The commonest histopathological change associated with cholelithiasis is chronic cholecystitis. Premalignant lesions are seen only in a small minority only. Hence early elective cholecystectomy can prevent malignant transformation in asymptomatic gall stones.